Global regulation of international intellectual property through Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS): The European Union and Brazil - Defossez, Delphine Aurélie Laurence (Journal of Law and Regulation, 2017)
Purpose ”“ This paper focuses on the regulation of copyrights at international level by comparing the situation under the TRIPS agreement in Brazil and in the European Union. Methodology/approach/design ”“ This article analyses standards and literature on regulation, as well as the role of TRIPS agreement. Attention was specially drawn to the market failure theory for justifying regulation, advocated by Baldwin & Cave. The TRIPS agreement will be analysed through Baldwin’s five criteria for good regulation. Findings ”“ The TRIPS agreement substantially widened the scope of governance of copyrights but imposes the WTO view on the matter. Notwithstanding its flaws, the TRIPS agreement remains the most comprehensive international agreement on intellectual property. According to Baldwin’s theory, the TRIPS agreement as a regulation is a good regulation. Indeed, it achieves the major part of the goals it set. However, some of the declared goals have never come to existence and had been replaced by other goals. On the overall, the TRIPS agreement has the capacity to regulate international intellectual property. Originality/value ”“ This paper analyses the TRIPS agreement as a way forward in the harmonization of the rules on intellectual property.